Liquid Chromatographic Tandem Mass Spectrometry Method for the Quantification of Miglitol in Human Plasma - Nirogi, Ramakrishna V. S.; Kandikere, Vishwottam N.; Shukla, Manoj; Mudigonda, Koteshwara; Maurya, Santosh; Boosi, Ravikumar; Yerramilli, Anjaneyulu (Arzneimittelforschung, 2006)
A rapid, sensitive and accurate liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the quantification of miglitol (CAS 72432-03-2), an α-glucosidase inhibitor, in human plasma using gabapentin (CAS 60142-96-3) as internal standard (IS). Following protein precipitation, the analytes were separated using an isocratic mobile phase on a reversed phase phenyl column and analyzed by MS in the multiple reaction monitoring mode using the respective [M+H]+ ions, m/z 208/146 for miglitol and m/z 172/154 for the IS. The assay exhibited a linear dynamic range of 100–6000 ng/mL for miglitol in human plasma. The lower limit of quantification was 100 ng/mL with a relative standard deviation of less than 5 %. Acceptable precision and accuracy were obtained for concentrations over the standard curve ranges. The average absolute recoveries of miglitol and the IS from spiked plasma samples were 40.5 ± 2.7 and 47.1 ± 2.9 %, respectively. A run time of 2.5 min for each sample made it possible to analyze a throughput of more than 400 human plasma samples per day. The validated method has been successfully used to analyze human plasma samples for application in pharmacokinetic, bioavailability or bioequivalence studies. The miglitol plasma concentration profile could be obtained for pharmacokinetic study. The observed maximum plasma concentration (Cmax) of miglitol (100 mg oral dose) is 1740 ng/mL, time to observed maximum plasma concentration (tmax) is 3.5 h and elimination halflife (t1/2) is 2.5 h.
Keywords: α-Glucosidase inhibitor; Antidiabetic drugs; CAS 72432-03-2; Miglitol, human plasma, liquid chromatography/tandem mass spectrometry, pharmacokinetic study